Implementation of active force control to disc brake for noise-free performance - Hashemi-Dehkordi, S. M.; Mailah, Musa; Abu Bakar, Abd. Rahim (Praise Worthy Prize S.r.l., 2009)

(untitled)
Disc brake noise is still considered an elusive problem in the automotive industry. To date, there are a number of solutions that have been proposed including modifying the structural and/or attaching the pad insulator but very few are successful. This paper attempts to describe an active method to reduce disc brake noise and vibration using an Active Force Control (AFC) strategy. A two degree-of-freedom (DOF) disc brake model is considered and adopted in the development of the proposed control system. First, the disc model is simulated and analysed using a conventional closed loop proportional-integral-derivative (PID) controller for vibration and noise control. Later, it is integrated with the AFC element that is designed to robustly reject the disturbances and uncertainties based on the given operating environment. It is found that the integrated PID-AFC scheme is very effective in suppressing the vibration and hence the noise compared to the pure PID controller. This paper also looks into the effect of negative damping on the brake performance